2010
DOI: 10.1002/app.32546
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of temperature‐sensitive block copolymers from poly(N‐isopropylacrylamide) and 4‐methyl‐ε‐caprolactone or 4‐phenyl‐ε‐caprolactone

Abstract: This study synthesizes thermally sensitive block copolymers poly(N-isopropylacrylamide)-b-poly(4-methyl-e-caprolactone) (PNIPA-b-PMCL) and poly(N-isopropylacrylamide)-b-poly(4-phenyl-e-caprolactone) (PNIPAb-PBCL) by ring-opening polymerization of 4-methyl-e-caprolactone (MCL) or 4-phenyl-e-caprolactone (BCL) initiated from hydroxy-terminated poly(N-isopropylacrylamide) (PNIPA) as the macroinitiator in the presence of SnOct 2 as the catalyst. This research prepares a PNIPA bearing a single terminal hydroxyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Moreover, the polymerization of γ-methyl-ε-caprolactone (γMCL) is known to be faster than γ-substituted ε-caprolactones with longer alkyl chains (ethyl, butyl, and propyl substituents) . The low glass transition temperature of PγMCL ( T g = −61 °C) has motivated the use of this polymer in biomedical applications. Combined, these attributes make PγMCL an interesting and desirable polymer to incorporate into PLA-TPEs. Moreover, γMCL can be synthesized through the Baeyer–Villiger oxidation of 4-methylcyclohexanone, a molecule that can ultimately be sourced from cresols.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polymerization of γ-methyl-ε-caprolactone (γMCL) is known to be faster than γ-substituted ε-caprolactones with longer alkyl chains (ethyl, butyl, and propyl substituents) . The low glass transition temperature of PγMCL ( T g = −61 °C) has motivated the use of this polymer in biomedical applications. Combined, these attributes make PγMCL an interesting and desirable polymer to incorporate into PLA-TPEs. Moreover, γMCL can be synthesized through the Baeyer–Villiger oxidation of 4-methylcyclohexanone, a molecule that can ultimately be sourced from cresols.…”
Section: Introductionmentioning
confidence: 99%
“…Ring-opening polymerization (ROP) of lactones has proven instrumental in the synthesis of sustainable aliphatic polyesters with attractive and competitive material properties when compared to petrochemically derived analogues. The uses for these polymers include tough thermoplastic elastomers, polyurethane foams, thermosets, elastomers, and block copolymer-based micelles. Given their versatility, there is a need to better understand how next-generation aliphatic polyesters are sourced and manufactured. Poly­(γ-methyl-ε-caprolactone) (PγMCL) has been employed for many of these applications due in large part to favorable polymerization kinetics and thermodynamics via metal-catalyzed ROP of γ-methyl-ε-caprolactone (γMCL), a low entanglement molar mass ( M e ), and potential biodegradability. , Moreover, several researchers have invoked facile retrosynthetic routes that would enable access to γMCL, among other valuable molecules, from sustainable biomass-derived feedstocks. In particular, lignin represents an enticing starting material due to its abundant supply and a surfeit of sources that generate it as a by-product of industrial scale processes, such as paper pulp refining and the lignocellulose-to-ethanol process. , Lignin bio-oils are the depolymerization products of lignins and are complex mixtures, comprised of hundreds of phenolic and cyclic aromatic compounds, the composition of which varies widely depending on such factors as lignin feedstock type, depolymerization method, heating rate, reaction temperature, and catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Poly­(4-methyl-ε-caprolactone) and poly­(6-methyl-ε-caprolactone) (PMCL) are hydrophobic polymers that are structurally similar to PCL but with a methyl group on each repeat unit that disrupts the ability of the chains to close-pack. , Therefore, in contrast to PCL, both PMCL isomers are amorphous, low- T g polymers. The synthesis, properties, self-assembly, and drug delivery applications of amphiphilic block copolymers based on PMCL hydrophobic blocks have been described by several groups. In addition, Wang et al reported the copolymerization of 4-methyl-ε-caprolactone (MCL) and ε-caprolactone (CL) to generate hydrophobic P­(MCL- co -CL) random copolymers with various ratios of MCL and CL monomers; characterization of their physical and biomedical properties (including degradability and biocompatibility) suggested that such copolymers with variable MCL contents could offer interesting and variable properties for biomedical applications, including drug delivery . However, to induce amphiphilic self-assembly, hydrophobic random copolymers of this type would need to be joined to a hydrophilic polymer block such as PEO.…”
Section: Introductionmentioning
confidence: 99%